A simulation-based method to inform serosurvey designs for estimating the force of infection using existing blood samples - Vicco,A; McCormack,CP; Pedrique,B; Amuasi,JH; Awuah,AA-A; Obirikorang,C; Struck,NS; Lorenz,E; May,J; Ribeiro,I; Malavige,GN; Donnelly,CA; et al. (PLoS Computational Biology, 2023)
The extent to which dengue virus has been circulating globally and especially in Africa is largely unknown. Testing available blood samples from previous cross-sectional serological surveys offers a convenient strategy to investigate past dengue infections, as such serosurveys provide the ideal data to reconstruct the age-dependent immunity profile of the population and to estimate the average per-capita annual risk of infection: the force of infection (FOI), which is a fundamental measure of transmission intensity.In this study, we present a novel methodological approach to inform the size and age distribution of blood samples to test when samples are acquired from previous surveys. The method was used to inform SERODEN, a dengue seroprevalence survey which is currently being conducted in Ghana among other countries utilizing samples previously collected for a SARS-CoV-2 serosurvey.The method described in this paper can be employed to determine sample sizes and testing strategies for different diseases and transmission settings.